ESL Students’ Perspectives on Language Anxiety - Abdul Aziz, Noor Hashima (2007)
The purpose of this study was to investigate the language anxiety experiences of students studying English as a second language (ESL) at Universiti Utara Malaysia. This study adopted a qualitative case study approach. The sampling of participants was done through purposive sampling in order to select information-rich cases. The sampling strategy employed was maximum variation sampling to find common patterns among three levels of English language courses and related samples of student participants. Data collection was done through interviewing ESL students and lecturers and also analyzing documents. Nineteen students were interviewed to get their perspectives on the language anxiety phenomenon. In order to understand language anxiety, four components were investigated: the sources of language anxiety, anxiety reactions, coping strategies and effects of language anxiety. Three major themes, three minor themes and two unexpected themes emerged from this study in relation to the sources of language anxiety. It was discovered that the language anxiety experienced by the participants stemmed from the learners themselves, lecturers’ instructional practice, social and cultural influence. In terms of language anxiety reactions, seven themes emerged from this study. This study also found eight strategies used by the participants to cope with language anxiety. Explanation on the effects of language anxiety focused more on the subtle effects based on the experiences shared by the participants in this study. The study concluded that language anxiety is a prevalent phenomenon among the participants. All the participants expressed experiencing anxiety but at various degrees such as low, moderate or high. Speaking and writing were the two language skills most associated with sources of language anxiety. Debilitating anxiety was a common experience among the participants with one exception. Some implications for the learners, lecturers, peers, and course developers are stated briefly. Some recommendations are also suggested for further study.